Corporate Image and Reputation in the Shipping Industry in Four Asian Countries: Republic of Korea, China, Japan, and Thailand - Hyunmi Jang; Ho Park; Sang Youl Kim; Pairach Piboonrungroj (International Journal of Supply Chain Management, 2019)
This study aims to analyze the perceptions regarding shipping companies corporate image and reputation in Republic of Korea, China, Japan, and Thailand. For this study, the shipping industry is confined to the bulk and container shipping sectors to prevent confusion arising from the different sectors. An international questionnaire survey was administered in each country. The participants were asked to report their perceptions on eight indicators of corporate image and seven indicators of corporate reputation relating to the shipping companies. Descriptive analyses and a one-way between-groups analysis of variance (ANOVA) were conducted using SPSS 20. Findings show that there are significant differences in perceptions concerning corporate image and reputation among four countries. Some cases show significant differences in the analyses in line with demographic characteristics. While China shows the highest scores in most variables, Korea is revealed to have the lowest scores. The results indicate the need to develop programs for improving the external positive perceptions of the shipping companies, as well as to broaden the scope of marketing activities targeting the general public. This study is of critical importance as it discusses relatively ignored but important issues by conducting comparative research in four major Asian countries comprehensively, particularly targeting samples rarely considered in the empirical shipping-related studies despite their significance to academic development. Further research is required to demonstrate the effectiveness of the findings by applying the measures in different national contexts with a more diverse group of samples.